LANGUAGE LEARNING STRATEGIES USED BY ADULT LEARNERS OF TEACHING ENGLISH AS A SECOND LANGUAGE (Academia Science Repository, 2023)
Learning a new language is a daunting task, especially when we are adults. The process of language acquisition is complex and requires commitment, time, and effort. Adult learners of Teaching English as a Second Language (TESOL) face myriad challenges as they tread through the learning journey. They have specific needs and motivations for learning English. In view of these complexities, language learning strategies (LLS) are essential for learners to make progress in their learning. This article aims to evaluate the language learning strategies used by adult learners of TESOL, how they are influenced by the context, culture, and personality of the learners.